Pengembangan E-LKPD pada materi Segitiga Melalui Eksplorasi Bangunan Rumah Bari Pangkalan Balai - Wulandari, Ayu; Afgani, Muhammad Win; Komarudin, Komarudin (Mandalika Mathematics and Educations Journal, 2024)
This research aims to produce an E-worksheet on triangular material through a valid and practical exploration of new houses in South Sumatra. The type of this research is Research and Development using the Tessmer development model. The research procedure focuses on the preliminary and the prototyping stages using a formative evaluation flow. This research procedure begins with problem identification and needs analysis to formulate objectives. Initial design and prototype development were carried out based on this analysis. The prototype was evaluated formatively using a formative evaluation flow carried out at the self-evaluation, expert review, one-to-one, small group, and field test stages. Validity data is obtained from validation sheets along with comments and suggestions from validators at the expert review stage, then practicality is obtained from the results of questionnaires and interviews at the one-to-one, small group, and field test stages. The subjects of this research were class VII students at SMP Negeri 2 Sembawa. The results of the research show that the E-worksheet developed meets the validity category reaching 86% with the very valid category and meets the practicality category reaching 92% with the very practical category, so it is concluded that the E-worksheet on triangle material through the exploration of new houses in South Sumatra is declared valid and practical.